1990
DOI: 10.1111/j.2044-8260.1990.tb00904.x
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive responses and the control of post‐operative pain

Abstract: This paper examines the relationship between spontaneous cognitive responses and reported pain experience in an acute pain population. Fifty-two patients, admitted for planned major surgery, had their pain intensity, distress and coping responses assessed 48 hours post-operatively. Significant correlations were obtained between negative responses and ratings of pain intensity and distress. No significant correlation was obtained between the analgesic dose and any other variable. The implications of the finding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
4
0

Year Published

1996
1996
2010
2010

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 5 publications
1
4
0
Order By: Relevance
“…Our outcome variables: pain reports, morphine consumption and satisfaction with pain relief were essentially unrelated. These findings correspond with reports in other studies on the weak associations between reported pain intensity and satisfaction with pain relief (Cohen, 1980;Ward and Gordon, 1994;Hawkins, 1997), and between pain reports and analgesic doses (Pick et al, 1990). Pellino and Ward (1998) found among surgery patients that perceived control partially mediated the relationship between reported pain severity and satisfaction.…”
Section: Clinical Significance Of the Findingssupporting
confidence: 92%
“…Our outcome variables: pain reports, morphine consumption and satisfaction with pain relief were essentially unrelated. These findings correspond with reports in other studies on the weak associations between reported pain intensity and satisfaction with pain relief (Cohen, 1980;Ward and Gordon, 1994;Hawkins, 1997), and between pain reports and analgesic doses (Pick et al, 1990). Pellino and Ward (1998) found among surgery patients that perceived control partially mediated the relationship between reported pain severity and satisfaction.…”
Section: Clinical Significance Of the Findingssupporting
confidence: 92%
“…Although it has not been tested directly to date, the possibility that emotional distress is a mediator of beneficial hypnotic effects on postsurgical outcomes is plausible for two reasons: (a) Higher levels of emotional distress are predictive of higher levels of postsurgical side effects (e.g., pain, nausea, and fatigue), and (b) hypnosis is effective in reducing emotional distress related to medical procedures. In a large number of studies with a variety of patient populations, surgical patients’ presurgery levels of emotional distress significantly predicted postsurgery pain (Arntz, van Eck, & Heijmans, 1990; Croog, Baume, & Nalbandian, 1995; Kain, Servarino, Aleander, Pincus, & Mayes, 2000; Katz et al, 2005; Martinez-Urrutia, 1975; Nelson, Zimmerman, & Barnason, 1998; Pick, Pearce, & Legg, 1990; Scott, Clum, & Peoples, 1983; Thomas, Robinson, Champion, McKell, & Pell, 1998). For example, Croog et al (1995) found that presurgery distress predicted postsurgery pain in dental patients; presurgery state anxiety has been associated with postsurgery pain in cholecystectomy patients (Scott et al, 1983); and Pick et al (1990) have reported that presurgery distress predicted postsurgery pain intensity in abdominal surgery patients.…”
mentioning
confidence: 99%
“…In a large number of studies with a variety of patient populations, surgical patients’ presurgery levels of emotional distress significantly predicted postsurgery pain (Arntz, van Eck, & Heijmans, 1990; Croog, Baume, & Nalbandian, 1995; Kain, Servarino, Aleander, Pincus, & Mayes, 2000; Katz et al, 2005; Martinez-Urrutia, 1975; Nelson, Zimmerman, & Barnason, 1998; Pick, Pearce, & Legg, 1990; Scott, Clum, & Peoples, 1983; Thomas, Robinson, Champion, McKell, & Pell, 1998). For example, Croog et al (1995) found that presurgery distress predicted postsurgery pain in dental patients; presurgery state anxiety has been associated with postsurgery pain in cholecystectomy patients (Scott et al, 1983); and Pick et al (1990) have reported that presurgery distress predicted postsurgery pain intensity in abdominal surgery patients. However, the contribution of emotional distress to postsurgical side effects may not be limited to postsurgical pain.…”
mentioning
confidence: 99%
“…In a large number of studies across a variety of patient populations, preoperative levels of emotional distress have been shown to predict levels of postoperative pain (e.g., Arntz, van Eck, & Heijmans, 1990; Croog, Baume, & Nalbandian, 1995; Martinez-Urrutia, 1975; Nelson, Zimmerman, & Barnason, 1998; Pick, Pearce, & Legg, 1990; Scott, Clum, & Peoples, 1983; Thomas, Robinson, Champion, McKell, & Pell, 1998). For example, preoperative distress has been reported to predict postoperative pain in 42 dental patients (Croog et al, 1995), preoperative state anxiety (but not trait) has been reported to predict postoperative pain levels in 48 cholecystectomy patients (Scott et al, 1983), and preoperative distress has been reported to predict postoperative pain intensity in 52 abdominal surgery patients (Pick et al, 1990). Presurgery distress has also been linked to increased postsurgery morphine dosages (Yang, Clark, Tsui, Ng, & Clark, 2000).…”
mentioning
confidence: 99%